1987
DOI: 10.1161/01.hyp.10.3.254
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, the renin-aldosterone system, and the hypotensive response to nifedipine.

Abstract: SUMMARY Ionic, hormonal, and blood pressure responses to a single oral dose of the calcium channel blocker nifedipine were assessed in 25 essential hypertensive subjects. When grouped according to their renin-sodium profile, low renin subjects had a greater hypotensive response to nifedipine (change in diastolic blood pressure -20.0± 1.4 vs -6.4 ± 1.0%; p<0.005) than did high renin hypertensive subjects. The initial level of serum ionized calcium predicted the blood pressure response to nifedipine (r = 0.70, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 13 publications
(11 reference statements)
3
11
0
Order By: Relevance
“…Lastly, this study provides a cellular ionic basis for the enhanced antihypertensive efficacy of calcium channel blockade previously noted in volume-dependent hypertensive states such as DOC-saline and Dahl salt-sensitive rat models and in essential hypertensive subjects with low plasma renin activity and/ or lower serum ionized calcium values (19,20,50). We have previously suggested that the lower average extracellular ionized calcium observed in the low renin state reflects a greater dependence of blood pressure on cytosolic calcium accumulation from the extracellular space vis a vis from internal stores (5 1), hence explaining their greater sensitivity to calcium channel blocking agents such as nifedipine (50).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Lastly, this study provides a cellular ionic basis for the enhanced antihypertensive efficacy of calcium channel blockade previously noted in volume-dependent hypertensive states such as DOC-saline and Dahl salt-sensitive rat models and in essential hypertensive subjects with low plasma renin activity and/ or lower serum ionized calcium values (19,20,50). We have previously suggested that the lower average extracellular ionized calcium observed in the low renin state reflects a greater dependence of blood pressure on cytosolic calcium accumulation from the extracellular space vis a vis from internal stores (5 1), hence explaining their greater sensitivity to calcium channel blocking agents such as nifedipine (50).…”
Section: Discussionmentioning
confidence: 86%
“…We have previously suggested that the lower average extracellular ionized calcium observed in the low renin state reflects a greater dependence of blood pressure on cytosolic calcium accumulation from the extracellular space vis a vis from internal stores (5 1), hence explaining their greater sensitivity to calcium channel blocking agents such as nifedipine (50). This present study provides additional evidence in favor of this hypothesis, by directly demonstrating in RBCs devoid of intracellular calcium stores, the linked blood pressure and cellular calcium elevating effects of salt loading and the reversal of these pressure and calcium effects by nifedipine.…”
Section: Discussionmentioning
confidence: 99%
“…Resnick et al, however, have reported a negative correlation between the extent of blood pressure reduction after nifedipine administration and pre-treatment PRA. 15) One reason for this disagreement could be the difference in the distribution of pre-treatment PRA between these studies. It was reported that salt intake was high in the Japanese population and low-renin hyperten- Fig.…”
Section: Discussionmentioning
confidence: 98%
“…3) It has been reported that antihypertensive drugs such as angiotensin receptor blockers (ARB), [8][9][10] angiotensin converting enzyme (ACE) inhibitors, 11,12) and b-blockers 13) reduce blood pressure more in hypertensive patients with a higher pre-treatment PRA. In contrast, diuretics 6,14) and calcium channel blockers (CCB) 15) show a more antihypertensive response in patients with a low-renin state. In these studies, however, the antihypertensive agents were not administered in a crossover fashion, and therefore whether the observed average trends are also reproducible in each individual patient has not yet been clearly demonstrated considering that essential hypertension is a heterogeneous disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertensive subjects with the opposite metabolic profile (high-renin activity, high serum ionized calcium and low 1,25-dihydroxy vitamin D levels) are relatively insensitive to the BP effects of both dietary salt loading and nifedipine, and show no significant hypotensive response to calcium supplements. [10] These results suggest that low-renin hypertension is more critically dependent on extracellular calcium than the highrenin type and demonstrate that both levels of serum ionized calcium and PRA may predict the sensitivity of BP to calcium channel blockade. [10] The CCBs have a wide spectrum of effects on the kidney.…”
Section: Calcium Antagonists (Calcium Channel Blockers)mentioning
confidence: 66%